Analisis penggunaan media google sites dalam implementasi pembelajaran berdiferensiasi pada materi teks deskripsi kelas IV sekolah dasar - Putriana Dafa Puspitawati; Rukayah Rukayah; Septi Yulisetiani (Didaktika Dwija Indria, 2024)
This research aims to describe the use of media in the implementation of differentiated learning. Google sites as a differentiated learning media in elementary schools. This research uses a qualitative approach with a case study method. The subjects in this research were fourth grade teachers and students. Data collection in this research was by observation, interviews, questionnaires and documentation. The validity test in this research is triangulation of sources and techniques. Data analysis in this research uses the Miles and Huberman interactive model. The research results show that using Google Sites as a learning medium has succeeded in making things easier for teachers and students because Google Sites has many features and can be used as learning and evaluation material. Students are able to access media that is tailored to their learning style, whether auditory, kinesthetic or visual. The responses shown by students included students becoming more active, the class becoming interactive, and teachers and students collaborating with each other.